Efforts Of Housewives In Increasing Household Income Through E-Commerce During The Pandemic In Solok City - Seftia Neri Tia; Yanti Karmila Nengsih (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This study aims to describe how the efforts of housewives in increasing family income through staying up late online in Tanjung Harapan District, Solok City. This type of research in descriptive with a qualitative approach. Data collection methods in this study are observation, interviews and documentation. The subjects of this research are hoisewives who do business online trading with the criteria of housewives who sell donuts, claw firecrackers, boba and salad. The results of research conducted on housewives in increasing family income through online trading business during the pandemic in Tanjung Harapan District, Solok City indicate that the efforts made by housewives in helping their husbands increase family income use social media accounts to promote their wares such as WhatsApp, Facebook and Instagram social media accounts.Keywords: Efforts of Housewives, Dual Roles, Increase Income